Hubungan Perilaku Gotong Royong dengan Sikap Integrasi Nasional Peserta Didik Kelas X di SMA Batik 1 Surakarta - Isnaini, Illahika Qurotul; Winarno; Noventari, Widya (CV. Kurnia Grup, 2024)
Various current developments have caused various phenomena of civic character that are in accordance with the spirit of Pancasila to begin to fade, one of which is mutual cooperation behavior. This is certainly not in accordance with the basic guidelines of the Indonesian state, namely Pancasila, which is closely linked to the spirit of unity. The problem of low levels of mutual cooperation behavior was discovered by researchers based on observations made on class X students at SMA Batik 1 Surakarta. The decline in mutual cooperation between students is characterized by a lack of caring attitude, egoism of students who prioritize their own interests, individualistic attitudes, and low awareness of students' responsibilities in a collaborative project. Given the related problems, it is necessary to strengthen mutual cooperation behavior among the nation's generations through education. One of them is through Pancasila Education as part of Citizenship Education. This research is research with a correlational quantitative approach. This research aims to prove whether there is a relationship between mutual cooperation behavior and the attitude of national integration of class X students at SMA Batik 1 Surakarta. The variables in this research are mutual cooperation behavior and national integration attitudes. The population in this study was all students in class X SMA Batik 1 Surakarta, totaling 450. The sample in this study was 84 students in classes X-5 and Data collection techniques through questionnaires. Data analysis uses normality, linearity and hypothesis testing. The results of the research show that there is a significant relationship between mutual cooperation behavior and the attitude of national integration of class X students at SMA Batik 1 Surakarta. These results are marked with R, namely 0.603 and a Sig value. namely 0.00. The correlation of behavior and attitudes in the results of this research strengthens the Theory of Planned Behavior. In other words, students' good mutual cooperation behavior correlates with their attitude of national integration in the good category as well.